KASUS RECESSIVE DYSTROPHIC EPIDERMOLYSIS BULLOSA-MITIS YANG TERDIAGNOSIS PADA SAAT LANJUT USIA (Perhimpunan Dokter Spesialis Kulit dan Kelamin Indonesia (PERDOSKI), 2023)
Introduction: Recessive dystrophic epidermolysis bullosa (RDEB) is a rare bullous disease caused by mutations in the COL7A1 gene encoding anchoring fibril collagen that maintains skin integrity. Case: Male, 67-year-old, presented with blisters and wound on various parts of the body, worsening in the recent year. They had been known to easily appear after trauma since. Vesicles-bullae, erosions-excoriations, milia, and atrophic scars were found on the axillae, groins, and limbs, as well as hyperkeratosis and anonychia of the hands and. Histopathological examination showed subepidermal cleft, milia and fibrosis, without immunoglobulin deposits on immunofluorescence. Discussion: Contrary to classical RDEB, blisters in mitis variant do not always cause impairment. The pronounced symptoms in advanced age might be mistaken for epidermolysis bullosa acquisita. Negative immunoglobulin deposition is the diagnostic key, confirming that blister does not result from an autoimmune process, but rather, from trauma to the abnormal skin, more so by flattening of the rete ridges in the elderly. In the absence of definitive therapy, treatment is symptomatic. Conclusion: The diagnosis RDEB-mitis might be missed in geriatric. Correct diagnosis has implication on management because not only does RDEB-mitis require no immunosuppressant, measures to minimize blister formation is more important to save patient from complication.